2012
DOI: 10.1556/achrom.24.2012.3.9
|View full text |Cite
|
Sign up to set email alerts
|

First detailed quantification of silymarin components in the leaves ofSilybum marianumcultivated in egypt during different growth stages

Abstract: Summary.A high performance liquid chromatographic method was developed for the quantitative determination of the active components of silymarin in the leaves of Silybum marianum during different growth stages. In this study, taxifolin and six main active constituents in silymarin, including silydianin, silychristin, diastereomers of silybin (silybin A and B) and diastereomers of isosilybin (isosilybin A and B) were completely separated on a 5-µm ODS column (Luna, Phenomenex, USA) with a mobile phase consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…Omar et al (2012) studied the silymarin components in leaves and seeds of S. marianum during different growth stages in Egypt, and found that each kilogram of leaves collected during the pre-flowering stage yielded 5.82 g of the total flavolignans and 3.42 g of taxifolin which was found to be considerably higher than the concentrations obtained in similar studies during both flowering and fruiting stages. The same authors pointed out the possibility of using the leaves during the pre-flowering stage as a major source for the production of silymarin, taking the advantages of the huge weight of the leaves, the short period of cultivation time, and the good yield of silymarin.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Omar et al (2012) studied the silymarin components in leaves and seeds of S. marianum during different growth stages in Egypt, and found that each kilogram of leaves collected during the pre-flowering stage yielded 5.82 g of the total flavolignans and 3.42 g of taxifolin which was found to be considerably higher than the concentrations obtained in similar studies during both flowering and fruiting stages. The same authors pointed out the possibility of using the leaves during the pre-flowering stage as a major source for the production of silymarin, taking the advantages of the huge weight of the leaves, the short period of cultivation time, and the good yield of silymarin.…”
Section: Introductionmentioning
confidence: 79%
“…Silymarin is an important free radical scavenger (Soto et al 2010) and it was detected in leaves and seeds of S. marianum during different growth stages (Omar et al 2012). On the other hand, Sanchez-Mata et al (2012) and Morales et al (2014) studied wild vegetables, traditionally eaten in the Mediterranean area, and indicated S. marianum, as a source of bioactive compounds such as polyphenols, vitamin C, organic acids, tocopherols, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that vegetable seed flours contain various antioxidant phytochemicals. Phenolic compounds have been found in broccoli, carrot, and milk thistle seed flours, including quercetin-3-glucoside, luteolin, and silymarin, respec-tively (Choe et al, 2018;Omar et al, 2012). Phenolic compounds possess the ability to donate hydrogen atoms and chelate metal ions, which gives them antioxidant activity (Balasundram et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin (Sm) is a signi cant free radical scavenger (Soto et al, 2010) which obtained from seeds and leaves of Silybum marianum (L.) Gaertn during its various stages of growth and development (Omar et al, 2012).The role of silymarin as a secondary metabolite which is a combination of six avonolignans i.e. (isosilybin A, B, Silybin A, B, Silychristin and Silydianin) have not been reported before but Sm is vital for improving the productivity of various plant since it widely accumulates plants in stressed conditions that increase the defense mechanism (Ghavami et al, 2008;Afshar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%